2023
DOI: 10.1007/s12144-022-04211-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychological and cognitive variables as well as cortisol levels in recovered Covid-19 patients: a longitudinal study

Abstract: Background: Decreased psychological and cognitive functioning is one of the complications of Covid-19 disease. We aimed to evaluate mental health, cognitive functioning, and salivary cortisol levels in Covid-19 patients with different disease severities in three 45-day intervals after recovery. Methods: 258 Covid-19 patients were assigned into three groups based on their disease severity: 112 patients in mild group, 67 patients in moderate group and 79 patients in severe group. The participants underwent psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Although counterintuitive at rst sight, this observation becomes more understandable if we consider that the pandemic has tested public health services, which have not been able to guarantee the psychological and psychiatric support necessary for situations of mild or modest severity, as the resources necessarily had to be allocated towards the more critical conditions. Arguably, this means that COVID-19 survivors who suffered from mild to moderate anxious or depressive symptoms, that were not adequately addressed, continued to manifest these symptoms even many months later, as suggested elsewhere [58, 70,39].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although counterintuitive at rst sight, this observation becomes more understandable if we consider that the pandemic has tested public health services, which have not been able to guarantee the psychological and psychiatric support necessary for situations of mild or modest severity, as the resources necessarily had to be allocated towards the more critical conditions. Arguably, this means that COVID-19 survivors who suffered from mild to moderate anxious or depressive symptoms, that were not adequately addressed, continued to manifest these symptoms even many months later, as suggested elsewhere [58, 70,39].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, although the WHO de nition considers the three-month term after the infection, some studies have reported the presence of at least one psychological symptom six months after the infection [29,30], or between six and twelve months [31][32][33][34][35][36][37], with some symptoms appearing to show a worsening trend over time [38,39]. Interestingly, two recent studies suggested the presence of physical (i.e., fatigue, dyspnea, headache, myalgia among the most reported) and psychological (i.e., anxiety, depression, cognitive problems, and sleep disturbance symptoms) consequences of COVID-19 after two years from the infection [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect of canonical inflammation in LC, which was not included in the aims and objectives of our study, is considering LC as a risk factor for the onset of various inflammatory diseases or the progression of existing inflammatory diseases [ 323 , 324 , 325 , 326 , 327 ]. This primarily concerns immune-dependent diseases, whose association has been established, namely various allergic, autoimmune, and infectious diseases, but also should be taken into account in other pathological conditions as well [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 ,…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, hypocortisolemia and hypoactivation of the HPA axis reported in LC are also reminiscent of what was previously described in 2005 in the post-SARS ‘sickness syndrome’ type condition characterized by symptoms such as malaise, anorexia, fatigue, and myalgias [ 246 ]. Improvement in cognitive functioning correlates with increased cortisol levels [ 247 ]. Furthermore, plasma cortisol levels have a significant negative correlation with fatigue scores and a positive correlation with quality of life [ 248 ].…”
Section: Local Phenomena Of Low-grade Inflammation In Lc and Other Vi...mentioning
confidence: 99%